ответ:1) (5а+3)+(-3а-4)=5а+3-3а-4=2а-1
(5а+ 3)-(-3а-4)=5а+3+3а+4=8а+7
2) (7х2+3х)+(-2х-1)=7х2+3х-2х-1=7х2+ 1х-1
(7х2+3х)-(-2х-1)= 7х2+3х+2х+1=7х2+ 5х+1
3)( 8b2 + 2b - 4)+( 5 - 3b - 9b2)= 8b2 + 2b – 4+5 - 3b - 9b2=-b2-b+1
( 8b2 + 2b - 4)-( 5 - 3b - 9b2)= 8b2 + 2b – 4 -5+3b+9b2=17b2+ 5b-9
4) (11y - 12 - y3)+( 14 - 12y + y3)= 11y - 12 - y3+14 - 12y + y3=-y+y3+2
(11y - 12 - y3)-( 14 - 12y + y3)= 11y - 12 - y3-14+12y-y3=23y-2y3-26
5) (6 + mn + 2)+( 4 - mn - m2)= 6 + mn + 2+4 - mn - m2=12-mn-m2
(6 + mn + 2)-( 4 - mn - m2)= 6 + mn + 2-4+mn+m2=4+2mn+m2
Объяснение:
не благодарите
1) -c√10; 2) 6√3 * a^8; 3) -x^9 * √-x; 4) √-b * b^10 * c^13
Объяснение:
1) -c√10 = √10 * |c| = √10 * (-c) т.к. c <= 0 по условию, поэтому: √10 * (-c) = -c√10
2)√108a^16 = √9 * 12 * (a^8)^2 = √9 * 4 * 3 *(a^8)^2 = 3√4 *3 * (a^8)^2 = 6√3 * √(a^8)^2 = 6√3 * |a^8| = 6√3 * a^8
3) √x^-19 = √-x * x^18 = √-x * (x^9)^2 = √-x * |x^9| = √-x * (-x^9) = -x^9 * √-x
4) √-b^21 * c^26 = √-b * b^20 * (c^13)^2 = √-b * √(b^10)^2 * √(c^13)^2 = √-b * |b^10| * |c^13| = √-b * b^10 * c^13
Если что-то не правильно, пишите.